(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents data from a field laboratory experiment conducted in the south of Uzbekistan in 2017-2020. Before sowing, soil moisture in the 0-30 cm layer averaged 13.6-14.3%, and in the arable layer 16.4-16.9% and the volumetric mass in the arable layer was 1.26-1.28 gramm cm3 , and in a layer of 30-50 cm 1.30-1.32 gramm cm3 . Soil moisture at the end of the growing season in the layer was 16.0-16.5% and the volumetric mass in the arable layer was 1.28-1.30 gramm cm3 and in the sub-arable layer 1.38-1.40 gramm cm3 . The water permeability of the soil before sowing oilseeds is 520-550 m3 ha-1 , in the initial state of the soil the humus content in the 0-30 cm layer was 0.669%, in the sub-arable soil layer 0.597%, total nitrogen, respectively, 0.054-0.059%, and gross phosphorus 0.124- 0.100%. The general state of nutrients after repeated (oilseed) crops showed a slight increase in their content. The humus content in the arable soil layer was 0.663-0.785%, the total nitrogen content in the 0-30 cm soil layer was 0.663-0.785%, the total nitrogen content in the 0-30 cm soil layer was 0.088-0.080%, in the under arable soil 0.050-0.069 %, and gross phosphorus, respectively, 0.130-0.139, and 0.124-0.127%, the content of humus, total nitrogen and gross phosphorus increased more after the cultivation of soybeans, peanuts and sunflowers, and a relatively low content was noted in the control (var. 1, 2) options.